THE IMPORTANCE OF COMPETITION IN THE FORMATION OF A FAVORABLE BUSINESS ENVIRONMENT (International Journal of Innovative Technologies in Economy, 2024)
In the realm of economic theory and practice, competition stands as a cornerstone in shaping a conducive environment for businesses. This article delves into the paramount importance of competition in fostering innovation, efficiency, and ultimately, economic growth. By analyzing the multifaceted impact of competition on market dynamics, consumer welfare, and industry evolution, it becomes evident that competitive forces play a pivotal role in driving businesses towards excellence and sustainability. Furthermore, the article explores the regulatory frameworks and policies essential for maintaining fair competition, thereby ensuring a level playing field for all market participants. Each independent state, which is a part of the global economy, tries to form a favorable business environment within its borders. It is impossible to form a favorable business environment without forming a favorable competitive environment. Research shows that there is a reciprocal relationship between competition and business. Because a favorable competitive environment forms a favorable business environment, the absence of a favorable business environment results in a favorable competitive environment not being fully formed in that region. In this regard, the article talks about the interaction of both concepts, as well as the exceptional importance of competition in the formation of a favorable business environment. The author considers a favorable competitive environment as a trigger factor for a favorable business environment. In the article, a statistical table was formed with reference to the statistical indicators of the international economic form for the comparison of competitiveness at the global level by evaluating competition, interindustry and intra-industry from different aspects and competitiveness between countries was evaluated from different aspects.